Knowledge of obstetric danger signs and associated factors among pregnant women attending antenatal care services at Thai community hospital [version 2; peer review: 2 approved] - Pruk Koovimon; Thanapob Bumphenkiatikul; Kasiphak Kaikaew; Khanittha Mahoree (F1000Research, 2023)
Background: To decrease preventable maternal mortality, providing health education to all parties is mandatory. Good knowledge, including awareness of pregnant women regarding obstetric danger signs (ODS), leads to appropriate practices and services. The knowledge of ODS varies among countries and regions. Since the data in rural regions of Thailand remains unavailable, this study aimed to identify the prevalence of good ODS knowledge and associated factors among pregnant women attending antenatal services at a Thai community hospital. Methods: We performed a cross-sectional, analytical study in 415 singleton pregnant women who visited the antenatal clinic at Wang Saphung Hospital, Loei, Thailand. A well-trained research assistant interviewed all participants using the data record form containing twenty items on the demographic and obstetric data and sixteen items on ODS knowledge. An ODS score of at least 75% (12 points) was considered a good level of knowledge. Results: A total of 275 participants (66.27%) had good knowledge of ODS. The most recognized ODS was vaginal bleeding whereas the least recognized ODS during pregnancy was convulsion; the least recognized ODS during labor and delivery was retained placenta. Multivariate regression analysis showed that the predictive factors of good OBS knowledge included a higher education level, maternal age of at least 20 years, and having medical personnel as a source of knowledge. Conclusions: In a rural setting of Thailand, two-thirds of pregnant women had good ODS knowledge. Identifying those at risk for fair and poor ODS knowledge and prompt management for the vulnerable subgroups might help decrease maternal mortality.